BRAND IMAGE, PRICE PERCEPTION AND QUALITY OF KECAP ABC PRODUCTS INFLUENCE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION IN GIANT KEDUNGSARI SURABAYA - Rosita Oktafiani; Ida Bagus Cempena (Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to determine whether there is an influence between the variables of Brand Image, Price Perception, Product Quality on Customer Loyalty through Customer Satisfaction at Giant Surabaya. Thisresearch method is explanatory research with hypothesis testing. The population in this study are the visitors who shop for Giant Kedungsari Surabaya, with sample of 100 computed by Slovin formula. Data collected by using a survey method with questionnaire as instrument. The analysis technique used is multiple linear regression analysis and t-test for test the hypothesis. The results of the study show that brand Image has a significant influence on Customer Satisfaction, Brand Image has no significant influence on Customer Loyalty, Price perception has a significant effect on customer satisfaction and loyalty, Product quality has a significant influence on customer satisfaction, but has no significant effect on customer loyalty, Customer Satisfaction has a significant influence on Customer Loyalty. This indicates that to increase customer satisfaction and loyalty, a good brand image, low price perception, good product quality, is needed.